EFEKTIVITAS BERBAGAI KONSENTRASI EKSTRAK DAUN KAYU MANIS (Cinnamomum burmannii [Ness.] BI) TERHADAP DIAMETER ZONA HAMBAT PERTUMBUHAN BAKTERI Staphylococcus epidermidis - Moh. Syaifuddin Qomar; Moch. Agus Krisno Budiyanto; Sukarsono Sukarsono; Sri Wahyuni; Husamah Husamah (Biota, 2018)
Staphylococcus epidermidis is one of the bacteria that can cause infectious diseases. In general Staphylococcus epidermidis can cause diseases of swelling (abscess) such as skin infections or acne. Cinnamon (Cinnamomum burmannii [Ness.] BI) leaf extract has a substance which gives antimicrobial effects that can be used as an inhibitor of the Staphylococcus epidermidis bacteria’s growth because it contains substances such as essential oils, flavonoids, saponins, tannins, and alkaloids. The aim of this research is to analyse the effect of the concentration of cinnamon leaf extract and to determine the concentration of extract which has the best influence to the inhibition zone diameter of Staphylococcus epidermidis bacteria. This research was conducted in Biology Laboratory of University of Muhammadiyah Malang, on 17-18 May 2017. The results showed that there was an effect of giving various concentrations of cinnamon leaf extract to the inhibition zone diameter of Staphylococcus epidermidis bacteria’s growth. The concentration of cinnamon leaf extract which has the best influence to the inhibitory zone diameter of Staphylococcus epidermidis bacteria is 100% with the mean of inhibitory zone diameter 15.16 mm.